Pemantauan Produksi Telur Ayam Perhari Melalui Jaringan Internet - Nobon Lazirsah Adnil; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Internet of Things (IoT) is a concept that utilizes the internet as a communication system to build intelligent interactions between people and objects around it. One of its application is in the field of animal husbandry. Along with its development, one of the farms that developed in Indonesia is laying hens. Many farmers still use the manual method to calculate egg production. This method is not efficient since it requires a lot of human resources to monitor and calculate the amount of egg production. This study presents the monitoring of chicken egg production based on IoT using Arduino microcontroller. Light Dependent Resistor (LDR) sensor was used as an input for detecting the chicken eggs, Espressif Smart Connectivity Platform (ESP) as the WI-FI module, Real Time Clock (RTC) as the timer and SD Card Module for data storage. All the data can be accessed by users on the ANTARES cloud platform by using the application on Android. Keywords: Arduino, Android,Monitoring